The Death of Gilles Deleuze as Composition of a Concept. Issue 1 (February 2017) - Beaulieu, Alain; Ord, Douglas
Abstract : There was a wide range of in memoriam and homages published in the years following Deleuze's suicide. However, none of them succeeded in grasping 'the evential' aspect of his death. This paper identifies a series of errors in the literature on Deleuze's death. It also suggests a way to overcome them by considering a singular encounter between Alice's passage through the looking glass and Deleuze's defenestration, which both took place on 4 November. We will show how a new conception of death as event comes out of this unseen connection.